KERANGKA DASAR AGAMA DALAM BUKU WAWASAN AL-QUR’AN KARYA M. QURAISH SHIHAB (KAJIAN AL-QUR’AN DENGAN PENDEKATAN SOSIOLOGI AGAMA) - Azizurrochim; Muh. Imam Sanusi Al Khanafi (CV. Doki Course and Training, 2023)
This article describes the basic framework of religion in the thoughts of M. Quraish Shihab as stated in his book Wawasan al-Qur'an. He explained comprehensively about religion which has a close relationship with the existing system in society. In this study the authors used qualitative methods (library research). From the results of the research it can be concluded that there are four basic frameworks designed by M. Quraish Shihab related to the issue of religion for humans, namely religion and a sense of security, religion and peace, religion and solidarity, religion and modernity. All the concepts about religion that are presented in his book in the big theme of religion, are strengthened by concepts brought by sociologists from Emile Durkheim, Max Weber, Williams James, Nottingham, and others. These concepts are accumulated strongly by the author of the book with several verses of the Koran and hadith. From the confessions of sociologists, they both think that religion will one day be needed when humans have fear. So that religion is present to provide a sense of security. Religion is also an institution built for the sake of social integration. Thus creating peace, not conflict. Religion in terms of solidarity is able to show the occurrence of cooperation and an important role reciprocally with all social institutions, both family, political, economic, legal and educational institutions. In terms of modernity, religion is one of the growth factors that has so far been able to drive transformational changes in the structure of the economy and society, contributing to development and advancing society. These are forms of actualization of religious values ​​regarding the economy in fulfilling responsibilities in society.